Laboratory characteristics analysis of the efficacy of levothyroxine on subclinical hypothyroidism during pregnancy: a single-center retrospective study. Issue 1 (1st January 2021) - Han, Luyang; Ma, Yan; Liang, Zhaoxia; Chen, Danqing
ABSTRACT: To reassess the efficacy of levothyroxine on subclinical hypothyroidism (SCH, 4.0 mIU/L ≤ TSH (thyroid stimulating hormone) <10 mIU/L with normal free T4) during pregnancy. 165 levothyroxine-treated pregnant women experiencing SCH were screened. And controls were randomly selected using euthyroidism (EU) women, matched by age, gravidity, and parity in the EU group ( n = 660). We evaluated laboratory characteristics and pregnancy outcomes during follow-ups. Compared with the EU group, the SCH group displayed higher inadequate maternal gestational weight gain, premature delivery, low birth weight offspring and infant offspring small for their gestational age. After levothyroxine treatment, the SCH group displayed lower total cholesterol, low-density lipoprotein levels, and higher serum homocysteine levels before delivery. Pregnant women with SCH still exhibit adverse pregnancy outcomes after levothyroxine treatment. Taken together, we believe that besides levothyroxine, vitamin B12 and folic acid could be added to the treatment of pregnant women with SCH. In addition, regular monitoring of blood sugar levels, lipid and homocysteine levels, and intervention gestational weight gain could alleviate the adverse effects of SCH on pregnancy outcomes. Graphical Abstract: uf0001